THE USE OF PROJECT MANAGEMENT METHODOLOGIES AND PROJECT RISK MANAGEMENT IN THE LIGHT OF EMPIRICAL RESEARCH - Brzozowski, Maciej (Management and Administration Journal, 2021)
The main purpose of the paper is to examine, on the basis of empirical research, the perceived manner of project management in organizations, as well as to determine the frequency of application of selected project management methodologies, in addition to the assessment of their usefulness for project risk management. The first part of the paper presents - identified on the basis of literature studies - types and examples of project management methodologies along with basic assumptions of the project risk management process, and in the second part - the results of empirical research conducted by recourse to a questionnaire among the participants of projects implemented in various types of organizations. The study showed that in organizations employing respondents, the methodical manner of project management is most often used, while the most popular project management methodologies were PMBoK, Agile and PRINCE2, wherein respondents highly rated the usefulness of selected methodologies for effective project risk management.